On the estimation of hysteretic energy demands for SDOF systems. - Arroyo, Danny (Earthquake engineering & structural dynamics.)
Based on a statistical study of the dynamic response of single degree of freedom (SDOF) systems subjected to earthquake ground motions, a rule to estimate hysteretic energy demands is proposed. Expressions for elastic?perfectly plastic, stiffness degrading and pinching SDOF systems were obtained. The proposed rule does not explicitly depend on the period of the system; instead, it depends on the elastic pseudo-acceleration and elastic velocity spectra. It is shown that the proposed rule can be applied to compute hysteretic energy demands for systems located at different soil conditions. In addition, information about scatter and bias of the proposed rule is also presented.